Positive electrode active material, positive electrode containing the same, and lithium secondary battery
By using lithium composite transition metal oxides containing nickel, cobalt, manganese and aluminum as the positive electrode active material, the problem of degradation of life characteristics of the high nickel content positive electrode active material is solved, and high energy density and long life battery performance is achieved.
Patent Information
- Application Number
- JP2024559527
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-07
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing high-nickel content positive electrode active materials have unstable structure during charging and discharging, resulting in a decrease in life characteristics, making it difficult to meet the needs of high energy density and long life.
The lithium composite transition metal oxide containing nickel, cobalt, manganese and aluminum is used as the positive electrode active material. The chemical composition and structure of the material are adjusted through coprecipitation reaction, heat treatment and other processes to achieve excellent structural stability and life characteristics.
The long-life characteristics of the cathode active material with high nickel content are achieved, the energy density and cycle stability of the battery are improved, and the service life of the battery is extended.
Smart Images

Figure 2025511915000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0043660 filed on April 7, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material, and a positive electrode and a lithium secondary battery containing the same, and more particularly to a positive electrode active material having improved life characteristics, and a positive electrode and a lithium secondary battery containing the same. [Background technology]
[0003] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.
[0004] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as the positive electrode active material of lithium secondary batteries. Among them, lithium cobalt oxide has the advantage of high operating voltage and excellent capacity characteristics, but the raw material cobalt is expensive and the supply is unstable, making it difficult to commercially apply it to large-capacity batteries. Lithium nickel oxide has poor structural stability and it is difficult to achieve sufficient life characteristics. On the other hand, lithium manganese oxide has excellent stability but poor capacity characteristics. Therefore, in order to compensate for the problems of lithium transition metal oxides containing Ni, Co, or Mn alone, lithium composite transition metal oxides containing two or more transition metals have been developed, and among them, lithium nickel cobalt manganese oxide containing Ni, Co, and Mn is widely used in the field of electric vehicle batteries.
[0005] Recently, the need for high-output, high-capacity batteries, such as those for electric vehicles, has been increasing, and as a result, the nickel content in the positive electrode active material is gradually increasing. When the nickel content in the positive electrode active material increases, the capacity characteristics improve, but when the charge and discharge are repeated, the highly reactive Ni 4+ A large amount of ions are generated, causing the structure of the positive electrode active material to collapse, which increases the rate of deterioration of the positive electrode active material and reduces the life characteristics.
[0006] Therefore, in order to realize high capacity, there is a need to develop a positive electrode active material that contains an excess amount of nickel and can realize excellent life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above-mentioned problems, and aims to provide a positive electrode active material having a high capacity with a molar ratio of Ni of 85 mol % or more among all metals other than lithium, and excellent structural stability that can realize long-life characteristics, as well as a positive electrode and a lithium secondary battery that include the positive electrode active material. [Means for solving the problem]
[0008] According to one embodiment, the present invention provides a positive electrode active material comprising a lithium composite transition metal oxide containing nickel, cobalt, manganese, and aluminum, the positive electrode active material comprising 85 mol % to 97 mol %, preferably 85 mol % to 95 mol %, and more preferably 90 mol % to 95 mol % of nickel and 2 mol % to 5 mol % of cobalt relative to the total number of moles of remaining metals other than lithium, and satisfying the following formula (1): Formula (1): 0.25≦I 550 / I 700 ≦0.4 In the formula (1), I 700 and I 550 respectively represent the 2D 7When the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is subjected to spectral analysis (peak deconvolution), it is the maximum peak intensity shown in the 600 to 800 ppm region and the maximum peak intensity shown in the 450 to 650 ppm region.
[0009] On the other hand, the 2D 7 The 1D NMR center band spectrum extracted from the Li MATPASS NMR spectrum has a first peak in the region from 550 ppm to 850 ppm and a second peak in the region from −10 ppm to 10 ppm.
[0010] Preferably, the positive electrode active material according to the present invention satisfies the following formula (1-1). Formula (1-1): 0.30≦I 550 / I 700 ≦0.4 In the formula (1-1), I 700 and I 550 is as defined in equation (1).
[0011] On the other hand, the 2D 7 When the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum was subjected to spectrum analysis (peak deconvolution), the maximum half-width (FWHM) of the peaks shown in the 600-800 ppm region was 700 ) is the maximum half-width (FWHM) of the peaks below 250 ppm and in the 450 to 650 ppm range. 550 ) is preferably 250 ppm or less, and the maximum half width (FWHM0) of the peak shown in the region of -10 to 10 ppm is preferably 50 ppm or less.
[0012] In addition, the positive electrode active material may contain 0.5 mol % or more and less than 5 mol % of manganese and 0.5 mol % or more and less than 5 mol % of aluminum relative to the total number of moles of remaining metals other than lithium, and specifically, may have a composition represented by the following [Chemical Formula 1]. [Chemical formula 1] Li a Ni b Co c Mn d Al e M 1 f O2 In the above [Chemical Formula 1], M 1 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0.8≦a≦1.2, 0.85≦b≦0.97, 0.02≦c≦0.05, 0.005≦d<0.05, 0.005≦e<0.05, and 0≦f≦0.02.
[0013] According to another embodiment, the present invention provides a method for producing a positive electrode active material, the method including: a first step of forming a precursor by co-precipitation of an aqueous transition metal solution containing nickel ions, cobalt ions, and manganese ions; a second step of mixing the precursor, a lithium source material, and an aluminum source material, followed by calcination to form a lithium composite transition metal oxide; and a third step of mixing the lithium composite transition metal oxide and a cobalt source material, followed by heat treatment to produce a positive electrode active material.
[0014] The ratio of the number of moles of cobalt contained in the cobalt source material in the third step to the number of moles of cobalt contained in the precursor in the first step may be 1 to 1.5.
[0015] In the third step, the heat treatment temperature may be 600°C to 750°C.
[0016] According to still another embodiment, the present invention provides a positive electrode comprising the positive electrode active material according to the present invention, and a lithium secondary battery comprising the positive electrode. Effect of the Invention
[0017] The positive electrode active material according to the present invention necessarily contains Ni, Co, Mn, and Al, the Ni content is 85 mol% to 97 mol%, the Co content is 2 mol% to 5 mol%, and the 2D 7 The maximum peak intensity I in the 600-800 ppm region when the 1D NMR center band spectrum extracted from the NMR spectrum obtained by Li MATPASS NMR analysis method was analyzed was 700 The maximum peak intensity in the range of 450 to 650 ppm for I 550 The ratio satisfies 0.25 to 0.4.
[0018] When Ni is contained at a high content of 85 mol % or more, it has the advantage of being able to realize a high energy density, but the surface of the positive electrode active material is highly reactive with Ni. 4+ As the amount of Co increases, side reactions with the electrolyte increase, structural stability decreases, and life characteristics rapidly deteriorate. However, as in the present invention, when Co is contained at a specific content and the peak characteristics of the NMR spectrum satisfy the condition of formula (1), excellent life characteristics can be realized even if Ni is contained at a high concentration. Therefore, by applying the positive electrode active material according to the present invention, a lithium secondary battery having high capacity and excellent life characteristics can be realized. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a diagram illustrating 1D NMR center band spectra extracted from NMR spectra obtained by analyzing the positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 by 2D 7Li MATPASS NMR analysis. [Diagram 2] FIG. 2 is a diagram showing NMR spectra obtained by analyzing the positive electrode active materials prepared in Example 1 and Comparative Example 1 by 1D Hahn-echo MAS NMR analysis. [Diagram 3]FIG. 2 is a diagram illustrating the results of spectrum analysis of a 1D NMR center band spectrum extracted from a 2D 7Li MATPASS NMR spectrum of the positive electrode active material of Example 1. [Figure 4] 1 is a graph showing the life characteristics of lithium secondary batteries to which the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2 are applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be specifically described below.
[0021] positive electrode active material The present inventors conducted extensive research to improve the life characteristics of high-nickel positive electrode active materials containing 85 mol % or more of Ni, and as a result, discovered that when the cobalt content in the positive electrode active material is 2 to 5 mol % and the ratio of coordination metals surrounding the lithium element is appropriately adjusted, the life characteristics of the high-nickel positive electrode active material is significantly improved, leading to the completion of the present invention.
[0022] Specifically, the positive electrode active material according to the present invention includes a lithium composite transition metal oxide containing nickel, cobalt, manganese, and aluminum, and in the positive electrode active material, the nickel content is 85 mol % to 97 mol % and the cobalt content is 2 mol % to 5 mol % relative to the total number of moles of remaining metals other than lithium, and satisfies the following formula (1):
[0023] Formula (1): 0.25≦I 550 / I 700 ≦0.4
[0024] In the formula (1), I 700 and I 550 respectively represent the 2D 7When the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is subjected to spectral analysis (peak deconvolution), it is the maximum peak intensity shown in the 600 to 800 ppm region and the maximum peak intensity shown in the 450 to 650 ppm region.
[0025] 2D in the present invention 7 The Li MATPASS NMR measurement conditions are as follows.
[0026] <Measurement conditions> Solid 400MHz WB (wide bore) NMR system MAS(magic angle spinning)rate:55kHz Spectral frequency(sfo1):155.62MHz( 7 Li) Temperature: ambient temperature 7 Li Chemical shift reference:secondary LiF(S)reference at -1ppm Pulse program: 2D MATPASS Spectral width(sw):1250kHz Acquisition time: 5 ms Carrier frequency (o1p) at 500ppm Pulse length(p1):1μs Recycle delay(d1): 35ms TD of F1 dimension(L1):8 Number of scans: 30000
[0027] After measurement, 2D data being processed by xfb and then a centerband slice ((L1 / 2+1)=(8 / 2+1)=5th slice) was taken.
[0028] On the other hand, 2D 7 Spectral analysis (peak deconvolution) of the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum can be performed using DMFIT (64bit, release♯20190125) NMR software. Specifically, the spectral analysis is 7 After importing the 1D NMR center band spectrum extracted from the Li MATPASS NMR spectrum into the DMFIT program, Gaussian / Lorentzian is selected as the fitting model for spectrum analysis, and appropriate initial values are set for the peak size (Amplitude), peak position (peak position), peak half width (width) and Gaussian / Lorentzian fraction (xG / (1-x)L), and fitting is repeated until an appropriate convergence value is reached. In the present invention, during spectrum analysis, the Gaussian / Lorentzian fraction (xG / (1-x)L) was fixed to 0.5, and fitting was performed under the conditions of nParVar=15, step=1, and Thresh=0.001.
[0029] Conventionally, one-dimensional (1D) solid-state 7Li NMR analysis was mainly used. However, the high-nickel positive electrode active material containing an excessive amount of Ni, a paramagnetic metal, was analyzed using 1D solid-state 7 When measuring using Li NMR analysis, the NMR resolution is reduced due to the influence of paramagnetism, and a phasing error occurs due to the overlap of the spinning sideband and the main peak, making it difficult to analyze the structural characteristics of the positive electrode active material (see Figure 2).
[0030] But 2D 7 By applying the Li MATPASS NMR analysis method, high-resolution NMR spectra can be obtained, and the structural features of the positive electrode active materials can be distinguished by spectral analysis of the extracted spectra. 7 As a result of analysis by Li MATPASS NMR analysis, it was found that a positive electrode active material formed so that the NMR spectrum satisfies the condition of the following formula (1) exhibits a significantly improved effect in terms of life characteristics.
[0031] 2D 7 The peak at around 700 ppm in the Li MATPASS NMR spectrum is a peak that appears when the metal arranged around Li in the crystal structure consists only of Ni, and the peak at around 550 ppm is a peak that appears when some of the metals arranged around Li in the crystal structure are Co and Al. On the other hand, when some of the metals arranged around Li are Mn, a peak appears at 700 ppm or more. Therefore, the peak intensity I 550 A high value of I means that the ratio of Co or Al arranged around lithium in the crystal structure is high, and the peak intensity I 700 A high I means that the proportion of only nickel atoms arranged around lithium in the crystal structure is high. 550 / I 700can be analyzed as a value corresponding to the ratio of Co arranged around lithium in the crystal structure.
[0032] According to the research of the present inventors, when a high-nickel positive electrode active material having a nickel content of 85 mol% to 97 mol% satisfies the condition of the above formula (1), the high-temperature life characteristics of a lithium secondary battery are significantly improved. 550 / I 700 In the case of a lithium secondary battery using a positive electrode active material in which I is in the range of 0.25 to 0.4, 550 / I 700 It was shown that, compared with lithium secondary batteries using positive electrode active materials in which R is less than 0.25 or exceeds 0.4, the capacity retention rate after 200 cycles at 45°C increased by 2 to 10% and the resistance increase rate decreased by 25% to 50%.
[0033] Although it is not clear why the effect of improving life characteristics is shown when the conditions of formula (1) are satisfied, it is speculated that this is because a certain ratio of cobalt out of the total cobalt contained in the positive electrode active material is arranged on the surface of the positive electrode active material, thereby suppressing changes in the crystal structure of the positive electrode active material during charge-discharge cycles, and because the ratio of cobalt among the metals arranged around lithium in the crystal structure satisfies a specific range, thereby increasing the stability of the crystal structure.
[0034] Preferably, the positive electrode active material satisfies the following formula (1-1): When the positive electrode active material satisfies the formula (1-1), the effect of improving the life characteristics is more excellent.
[0035] Formula (1-1): 0.30≦I 550 / I 700 ≦0.4
[0036] In the formula (1-1), I 700 and I 550 is as defined in equation (1).
[0037] More preferably, the positive electrode active material satisfies the following formula (1-2): When the positive electrode active material satisfies the formula (1-2), the effect of improving the life characteristics is more excellent.
[0038] Formula (1-2): 0.35≦I 550 / I 700 ≦0.4
[0039] In the formula (1-2), I 700 and I 550 is as defined in equation (1).
[0040] On the other hand, the positive electrode active material according to the present invention is 7 The 1D NMR center band spectrum extracted from the NMR spectrum obtained by the Li MATPASS NMR analysis method shows two peaks, specifically, the first peak in the region of 550 ppm to 850 ppm and the second peak in the region of -10 ppm to 10 ppm. This is a one-dimensional (1D) solid-state 7 This is in contrast to the NMR spectrum obtained by Li NMR analysis, which shows three or more peaks.
[0041] In addition, the 2D 7 When the 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is subjected to spectrum analysis (peak deconvolution), the full width at half maximum (FWHM) of the peak shown in the region of 600 to 800 ppm can be 250 ppm or less, preferably 70 to 230 ppm, and more preferably 100 to 200 ppm. 700) satisfies the above range, NMR peak information of Li surrounded only by Ni can be extracted with high accuracy during spectrum analysis, and local structural information of the positive electrode active material can be grasped more accurately.
[0042] In addition, the 2D 7 When the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning-Phase Adjusted Spinning Sideband) NMR spectrum is subjected to spectrum analysis (peak deconvolution), the full width at half maximum (FWHM) of the peak shown in the region of 450 to 650 ppm can be 250 ppm or less, preferably 70 to 230 ppm, and more preferably 100 to 200 ppm. 550 ) satisfies the above range, NMR peak information of Li partially coordinated with Co or Al can be extracted with high accuracy during spectrum analysis, and the local structure of the positive electrode active material can be grasped more accurately.
[0043] In addition, the 2D 7 When the 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is subjected to spectrum analysis (peak deconvolution), the full width at half maximum (FWHM0) of the peak shown in the region of -10 ppm to 10 ppm can be 50 ppm or less, preferably 5 to 45 ppm, and more preferably 10 to 30 ppm. When the full width at half maximum (FWHM) of the peak shown in the region of -10 ppm to 10 ppm satisfies the above range, diamagnetic Li peak information can be extracted with high accuracy during spectrum analysis, and the local structure of the positive electrode active material can be grasped more accurately.
[0044] Next, the composition of the positive electrode active material according to the present invention will be described.
[0045] The positive electrode active material according to the present invention includes a lithium composite transition metal oxide that includes nickel, cobalt, manganese, and aluminum.
[0046] The positive electrode active material may contain nickel in an amount of 85 mol% or more, preferably 85 mol% to 97 mol%, more preferably 85 mol% to 95 mol%, and even more preferably 90 mol% to 95 mol%, based on the total number of moles of the remaining metals other than lithium. When the nickel content in the positive electrode active material satisfies the above range, excellent capacity characteristics can be achieved.
[0047] The positive electrode active material may contain 2 mol% to 5 mol%, preferably 3 mol% to 4 mol% of cobalt based on the total moles of the remaining metals other than lithium. If the cobalt content is less than 2 mol% in a high-nickel positive electrode active material having a nickel content of 85 mol% or more, structural stability may decrease, long-term life characteristics may decrease, and resistance may increase, while if it exceeds 5 mol%, capacity may decrease.
[0048] The positive electrode active material may contain manganese in an amount of 0.5 mol% or more and less than 5 mol%, preferably 1 mol% or more and less than 5 mol%, more preferably 1 mol% to 3 mol%, based on the total number of moles of metals other than lithium. When the manganese content satisfies the above range, there are advantages in that the structural stability is excellent, and the catalytic reaction on the surface is suppressed, thereby suppressing gas generation.
[0049] The positive electrode active material may contain aluminum in an amount of 0.5 mol% to less than 5 mol%, preferably 1 mol% to less than 5 mol%, more preferably 1 mol% to 3 mol%, based on the total moles of metals other than lithium. If the aluminum content exceeds the range, it may cause a decrease in capacity, and if it is less than the range, it may cause a decrease in structural stability and surface stability, resulting in a decrease in life characteristics and an increase in resistance.
[0050] On the other hand, the positive electrode active material may contain, as necessary, a doping element M in addition to nickel, cobalt, manganese, and aluminum. 1 The doping element M 1 can be, for example, one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb.
[0051] Specifically, the positive electrode active material may have a composition represented by the following [Chemical Formula 1].
[0052] [Chemical formula 1] Li a Ni b Co c Mn d Al e M 1 f O2
[0053] In the above [Chemical Formula 1], M 1 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0.8≦a≦1.2, 0.85≦b≦0.97, 0.02≦c≦0.05, 0.005≦d<0.05, 0.005≦e<0.05, and 0≦f≦0.05.
[0054] Preferably, the b may be 0.85≦b≦0.95, or 0.90≦b≦0.95, the c may be 0.03≦c≦0.05, or 0.03≦c≦0.04, the d may be 0.01≦d<0.05 or 0.01≦d≦0.03, and the e may be 0.01≦e<0.05 or 0.01≦e≦0.03.
[0055] Method for producing positive electrode active material Next, a method for producing the positive electrode active material according to the present invention will be described.
[0056] The positive electrode active material according to the present invention having the above-mentioned composition and NMR peak characteristics can be prepared by adding the cobalt contained in the positive electrode active material in two stages at a specific molar ratio rather than adding it all at once.
[0057] Specifically, the method for producing a positive electrode active material according to the present invention includes a first step of forming a precursor by co-precipitation of an aqueous transition metal solution containing nickel ions, cobalt ions, and manganese ions, a second step of mixing the precursor, a lithium source material, and an aluminum source material, followed by calcination to form a lithium composite transition metal oxide, and a third step of mixing the lithium composite transition metal oxide and a cobalt source material, followed by heat treatment to produce a positive electrode active material.
[0058] First step First, a precursor is formed by co-precipitation of an aqueous transition metal solution containing nickel ions, cobalt ions, and manganese ions.
[0059] The transition metal aqueous solution can be prepared by dissolving a transition metal-containing raw material in a solvent such as water, for example, a nickel-containing raw material, a cobalt-containing raw material, or a manganese-containing raw material in water. 1 It may further comprise a metal source material.
[0060] Meanwhile, the transition metal-containing raw material may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, hydroxide, or oxide of a transition metal.
[0061] Specifically, the nickel-containing source material can be, for example, NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, nickel halides, or combinations thereof.
[0062] The cobalt-containing source material can be, for example, CoSO4, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4·7H2O, or combinations thereof.
[0063] The manganese-containing source material can be, for example, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halides, or combinations thereof.
[0064] Said M 1 The metal source material is, for example, M 1 The metal may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, or oxide, and M 1 can be one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb.
[0065] Here, the input amount of each of the transition metal-containing raw materials can be determined in consideration of the molar ratio of the transition metal in the final cathode active material to be produced. For example, in the present invention, the nickel-containing raw material can be input in an amount such that the nickel content of the total transition metals in the final cathode active material is 85 mol% or more, preferably 85 mol% to 97 mol%, more preferably 85 mol% to 95 mol%, and even more preferably 90 mol% to 95 mol%.
[0066] Meanwhile, the cobalt-containing raw material may be added in an amount that is 0.4 to 0.5 times the cobalt content in the final positive active material. In the present invention, only a portion of the cobalt contained in the positive active material is added during the coprecipitation reaction, and the remaining cobalt is added in a third step described below, which makes it possible to adjust the ratio of lithium coordinated with cobalt in the crystal structure compared to the case where all of the cobalt is added during the coprecipitation reaction.
[0067] Meanwhile, the ammonium cation complexing agent may include at least one compound selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and (NH4CO3)2, and may be added to the reactor in the form of a solution in which the compound is dissolved in a solvent. Here, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.
[0068] The basic compound may be at least one compound selected from the group consisting of NaOH, KOH, and Ca(OH)2, and may be added to the reactor in the form of a solution in which the compound is dissolved in a solvent, where the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.
[0069] As described above, when the aqueous transition metal solution, the ammonium cation complex forming agent and the basic compound are charged into a reactor and stirred, the transition metal in the aqueous transition metal solution is coprecipitated to produce precursor particles in the form of transition metal hydroxide.
[0070] Here, the aqueous transition metal solution, the ammonium cation complex forming agent and the basic compound are added in amounts such that the pH of the reaction solution falls within a desired range.
[0071] When the precursor particles are formed by the above method, the positive electrode active material precursor is separated from the reaction solution to obtain the positive electrode active material precursor. For example, the reaction solution is filtered to separate the positive electrode active material precursor from the reaction solution, and the separated positive electrode active material precursor is washed with water and dried to obtain the positive electrode active material precursor. Here, if necessary, a process such as pulverization and / or classification can be performed.
[0072] Second step Next, the positive electrode active material precursor is mixed with a lithium raw material and an aluminum raw material, and then calcined to prepare a lithium composite transition metal oxide.1 The metal-containing source materials can be mixed together and fired.
[0073] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, for example, Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, Li3C6H5O7, or a mixture thereof.
[0074] The aluminum-containing source material can be, for example, Al2O3, Al(OH)3, Al(NO3)3, Al2(SO4)3, (HO)2AlCH3CO2, HOAl(CH3CO2)2, Al(CH3CO2)3 aluminum halide, or combinations thereof.
[0075] Said M 1 The metal source material is, for example, M 1 The metal may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, or oxide, and M 1 can be one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb.
[0076] Meanwhile, the lithium source materials may be mixed in an amount such that the molar ratio of Li:Ni+Co+Mn+Al in the mixture is 1:1 to 1.2:1, preferably 1:1 to 1.1:1, and more preferably 1:1 to 1.06:1. When the mixing ratio of the lithium source materials satisfies the above range, the layered crystal structure of the positive electrode active material is well developed, and a positive electrode active material having excellent capacity characteristics and structural stability can be produced.
[0077] On the other hand, the firing can be carried out at a temperature of, for example, 650°C to 800°C, preferably 690°C to 770°C, in an oxygen atmosphere for 5 hours to 35 hours, preferably 8 hours to 20 hours. In this specification, the oxygen atmosphere means an atmosphere containing sufficient oxygen for firing, including an air atmosphere. In particular, it is preferable to carry out the firing in an atmosphere having an oxygen partial pressure higher than that of the air atmosphere.
[0078] Third step Next, the lithium composite transition metal oxide thus prepared is mixed with a cobalt raw material, and the mixture is heat-treated to prepare a positive electrode active material.
[0079] Here, the cobalt source material may be, for example, Co(OH)2, CoO, CoSO4, Co(NO3)2, CoCO3, Co3(PO4)2, etc.
[0080] Meanwhile, the cobalt source material may be mixed in an amount such that the ratio of the number of moles of cobalt contained in the cobalt source material in the third step to the number of moles of cobalt contained in the precursor in the first step is 1 to 1.5, preferably 1 to 1.3, and more preferably 1 to 1.2. When the ratio of the number of moles of cobalt added in the first step to the number of moles of cobalt added in the third step satisfies the above range, the ratio of lithium and cobalt coordinated in the crystal structure is adjusted, and a positive electrode active material satisfying formula (1) can be obtained.
[0081] In addition, the heat treatment temperature may be 600°C to 750°C, preferably 600°C to 700°C. When the heat treatment temperature satisfies the above range, the ratio of lithium and cobalt coordinated in the crystal structure is adjusted, and a positive electrode active material satisfying formula (1) can be obtained. The degree of diffusion of Co element changes depending on the heat treatment temperature, and thus the ratio of lithium and cobalt coordinated in the crystal structure changes. Therefore, in order to appropriately adjust the ratio of lithium coordinated with Co, the heat treatment temperature must be appropriately adjusted. When the heat treatment temperature is less than 600°C, the ratio of Co penetrating into the inside of the secondary particles of the positive electrode active material is excessively small, and when it exceeds 750°C, the content of Co diffused into the inside of the crystal lattice becomes excessively large, making it difficult to obtain a positive electrode active material satisfying formula (1).
[0082] As described above, a part of the total cobalt content contained in the positive electrode active material is added during the coprecipitation reaction for forming the precursor, and the remaining amount is added after the formation of the lithium transition metal composite oxide, and a heat treatment is performed at an appropriate temperature, thereby producing a positive electrode active material satisfying formula (1).
[0083] Also, although not required, if necessary, a coating layer forming step may be further performed after the third step. The coating layer forming step may be performed by mixing the positive electrode active material and the coating raw material and then heat treating the mixture.
[0084] The coating raw material may be acetate, carbonate, nitrate, sulfate, halide, sulfide or oxide containing a coating element, and the coating element may be, for example, one or more selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si and S.
[0085] Here, the mixing may be performed as a solid-phase mixing or liquid-phase mixing, and the heat treatment may be performed at a suitable temperature depending on the coating raw material, for example, the heat treatment in the coating process may be performed at a temperature of 200°C to 700°C or 300°C to 600°C, but is not limited thereto.
[0086] positive electrode Next, the positive electrode according to the present invention will be described.
[0087] The positive electrode according to the present invention includes a positive electrode active material layer including the positive electrode active material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0088] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0089] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.
[0090] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. One or a mixture of two or more of these can be used. The conductive material can be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight based on the total weight of the positive electrode active material layer.
[0091] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.
[0092] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode. For example, the positive electrode may be manufactured by mixing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, applying the positive electrode slurry onto a positive electrode current collector, and then drying and rolling the positive electrode slurry. Here, the types and contents of the positive electrode active material, binder, and conductive material are as described above.
[0093] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to have a viscosity that can dissolve or disperse the positive electrode active material, conductive material, and binder and provide excellent thickness uniformity during subsequent coating for the production of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0094] Alternatively, the positive electrode can be produced by casting the positive electrode slurry on a separate support, peeling the resulting film from the support, and laminating the film on a positive electrode current collector.
[0095] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.
[0096] The lithium secondary battery of the present invention includes the positive electrode according to the present invention. Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, the positive electrode being as described above. The lithium secondary battery may also optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0097] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0098] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0099] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0100] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the above-mentioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used.
[0101] Also, a metallic lithium thin film may be used as the negative electrode active material. Also, the carbon material may be either low crystalline carbon or high crystalline carbon. Typical low crystalline carbons are soft carbon and hard carbon, and typical high crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high temperature fired carbons such as petroleum or coal tar pitch derived cokes.
[0102] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery to be constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can usually be contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0103] The binder serves to improve the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0104] For example, the negative electrode active material layer may be manufactured by applying a negative electrode slurry containing a negative electrode active material, and optionally a binder and a conductive material, onto a negative electrode current collector and drying the applied negative electrode slurry, or by casting the negative electrode slurry onto a separate support, peeling the negative electrode slurry from the support, and laminating the resulting film onto the negative electrode current collector.
[0105] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.
[0106] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0107] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0108] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a C2-C20 straight-chain, branched or cyclic hydrocarbon group that can contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred.
[0109] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 can be used as the lithium salt. The concentration of the lithium salt is preferably within a range of 0.1 to 5.0M, preferably 0.1 to 3.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0110] In addition to the electrolyte components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, and improving the discharge capacity of the battery. For example, the additives may be haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcohol amine, cyclic ethers, ethylene diamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, which may be used alone or in combination, but are not limited thereto. The additives may be contained in an amount of 0.1 to 10% by weight, preferably 0.1 to 5% by weight, based on the total weight of the electrolyte.
[0111] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0112] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0113] The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0114] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0115] Example 1 A transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed to a molar ratio of Ni:Co:Mn of 92:2:2, an aqueous ammonia solution, and a sodium hydroxide solution were added to a coprecipitation reactor to form a precursor. The precursor particles were separated, washed, and dried to produce the precursor.
[0116] The precursor synthesized by the coprecipitation reaction was mixed with LiOH and aluminum hydroxide so that the molar ratio of Ni+Co+Mn:Al:Li was 96:2:98, and the mixture was fired in an oxygen atmosphere at 750°C for 12 hours to produce a lithium composite transition metal oxide.
[0117] The lithium composite transition metal oxide and Co(OH)2 were mixed in amounts such that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2, and then heat-treated at 650°C for 8 hours to prepare a positive electrode active material.
[0118] Example 2 A transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed to a molar ratio of Ni:Co:Mn of 92:2:2, an aqueous ammonia solution, and a sodium hydroxide solution were added to a coprecipitation reactor to form a precursor. The precursor particles were separated, washed, and dried to produce the precursor.
[0119] The precursor synthesized by the coprecipitation reaction was mixed with LiOH and aluminum hydroxide so that the molar ratio of Ni+Co+Mn:Al:Li was 96:2:98, and the mixture was fired in an oxygen atmosphere at 750°C for 12 hours to produce a lithium composite transition metal oxide.
[0120] The lithium composite transition metal oxide and Co(OH)2 were mixed in amounts such that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2, and then heat-treated at 600°C for 8 hours to prepare a positive electrode active material.
[0121] Comparative Example 1 A transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed to a molar ratio of Ni:Co:Mn of 92:4:2, an aqueous ammonia solution, and a sodium hydroxide solution were added to a coprecipitation reactor to form a precursor. The precursor particles were separated, washed, and then dried to produce the precursor.
[0122] The precursor synthesized by the coprecipitation reaction was mixed with LiOH and aluminum hydroxide so that the molar ratio of Ni+Co+Mn:Al:Li was 98:2:100, and the mixture was fired in an oxygen atmosphere at 750°C for 12 hours to produce a positive electrode active material.
[0123] Comparative Example 2 A transition metal solution in which NiSO4 and MnSO4 were mixed to a molar ratio of Ni:Mn of 92:2, an aqueous ammonia solution, and a sodium hydroxide solution were added to a coprecipitation reactor to form a precursor. The precursor particles were separated, washed, and then dried to produce the precursor.
[0124] The precursor synthesized by the coprecipitation reaction was mixed with LiOH and aluminum hydroxide so that the molar ratio of Ni+Mn:Al:Li was 94:2:96, and the mixture was fired in an oxygen atmosphere at 750°C for 12 hours to produce a lithium composite transition metal oxide.
[0125] The lithium composite transition metal oxide and Co(OH)2 were mixed in amounts such that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2, and then heat-treated at 650°C for 8 hours to prepare a positive electrode active material.
[0126] Experimental Example 1: NMR Spectroscopic Analysis 2D of the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 and 2 7 Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectra were obtained and the 1D NMR centerband spectrum was extracted.
[0127] FIG. 1 shows the 2D structure of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2. 7 The 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is shown in FIG. 2. For comparison, the 1D Hahn-echo MAS NMR spectra of the positive electrode active materials of Example 1 and Comparative Example 1 were measured and shown in FIG.
[0128] With reference to Figures 1 and 2, 7The 1D NMR centerband spectrum extracted from the NMR spectrum obtained by Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) analysis method has only two peaks in the 550 ppm to 850 ppm region and the -10 ppm to 10 ppm region, whereas the 1D Hahn-echo MAS NMR spectrum shows many more peaks as a result of magic angle spinning, and it can be confirmed that the spinning sidebands (indicated with *) generated in this way overlap with the main peak.
[0129] Next, the 2D 7 Spectral analysis of the 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning-Phase Adjusted Spinning Sideband) NMR spectrum revealed that the I 550 / I 700 value, and the maximum half-width (FWHM) of the peaks in the 600-800 ppm region 700 ), and the maximum half-width (FWHM) of the peaks in the 450-650 ppm region 550 ), and the maximum half-width (FWHM0) of the peak in the region of -10 to 10 ppm was measured. The measurement results are shown in [Table 1]. In addition, FIG. 7 The results of spectral analysis of the 1D NMR centerband spectrum extracted from the Li MATPASS NMR spectrum are shown.
[0130] On the other hand, the 2D 7 The conditions for measuring the Li MATPASS NMR spectrum and the conditions for spectrum analysis were as described above.
[0131] [Table 1]
[0132] Experimental example 2: Evaluation of high temperature life characteristics The positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, conductive material (Super C65), and PVDF binder were mixed in a weight ratio of 96.5:1.5:2 in N-methylpyrrolidone to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried, and rolled to prepare a positive electrode.
[0133] A mixture (weight ratio 5:5) of natural graphite (GT, Zichen) and artificial graphite (AGP8, BTR) as the negative active material, Super-C65 (Timcal) as the conductive material, SBR binder (BM-L302, Zeon), and additive (Daicel 2200, Daicel Chemical Industry) were mixed in water in a weight ratio of 95.6:1:2.3:1.1 to prepare a negative electrode slurry. The negative electrode slurry was applied to one side of a copper current collector, dried, and rolled to prepare a negative electrode.
[0134] An electrode assembly was prepared by interposing a separator between the positive and negative electrodes, and then the electrode assembly was placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving LiPF6 at a concentration of 1M in a mixed organic solvent in which ethylene carbonate / dimethyl carbonate / diethyl carbonate were mixed in a volume ratio of 1:2:1, and adding 2 wt% vinylene carbonate (VC).
[0135] Each of the lithium secondary batteries prepared above was charged at 45° C. in CC-CV mode at 0.3 C up to 4.25 V and discharged at a constant current of 0.3 C down to 2.5 V for 200 cycles, and then the capacity retention rate and the resistance increase rate were measured to evaluate the life characteristics. The measurement results are shown in FIG. 4.
[0136] Referring to Figure 4, I 550 / I 700The lithium secondary batteries using the positive electrode active materials of Examples 1 and 2, which satisfy the I 550 / I 700 The positive electrode active material of Comparative Example 1, in which I is greater than 0.4, and 550 / I 700 It can be seen that the battery exhibits superior life characteristics as compared to the lithium secondary battery using the positive electrode active material of Comparative Example 2, in which the positive electrode active material has a β-value of less than 0.25.
Claims
1. A positive electrode active material comprising a lithium composite transition metal oxide containing nickel, cobalt, manganese and aluminum, The positive electrode active material contains 85 mol % to 97 mol % of nickel and 2 mol % to 5 mol % of cobalt based on the total number of moles of metals other than lithium, A positive electrode active material that satisfies the following formula (1): Formula (1): 0.25≦I 550 / I 700 ≦0.4 In the formula (1), I 700 and I 550 respectively represent the 2D of the positive electrode active material. 7 Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is extracted from the 1D NMR center band spectrum by spectrum analysis (peak deconvolution). It is the maximum value of the peak intensity shown in the region of 600 to 800 ppm and the maximum value of the peak intensity shown in the region of 450 to 650 ppm.
2. The 2D of the positive electrode active material 7 2. The positive electrode active material according to claim 1, wherein the 1D NMR center band spectrum extracted from the Li MATPASS NMR spectrum has a first peak in the region of 550 ppm to 850 ppm and a second peak in the region of -10 ppm to 10 ppm.
3. The positive electrode active material according to claim 1, which satisfies the following formula (1-1): Formula (1-1): 0.30≦I 550 / I 700 ≦0.4 In the formula (1-1), I 700 and I 550 respectively represent the 2D of the positive electrode active material. 7 Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum is extracted from the 1D NMR center band spectrum by spectrum analysis (peak deconvolution). It is the maximum value of the peak intensity shown in the region of 600 to 800 ppm and the maximum value of the peak intensity shown in the region of 450 to 650 ppm.
4. The 2D of the positive electrode active material 7 When the 1D NMR centerband spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum was subjected to spectrum analysis (peak deconvolution), the maximum half-width (FWHM) of the peak shown in the region of 600 to 800 ppm was 700 2. The positive electrode active material according to claim 1, wherein the amount of ZnO is 250 ppm or less.
5. The 2D of the positive electrode active material 7 When the 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum was subjected to spectrum analysis (peak deconvolution), the maximum half width (FWHM) of the peak shown in the region of 450 to 650 ppm was 550 2. The positive electrode active material according to claim 1, wherein the amount of ZnO is 250 ppm or less.
6. The 2D of the positive electrode active material 7 When the 1D NMR center band spectrum extracted from the Li MATPASS (Magic Angle Turning Phase Adjusted Spinning Sideband) NMR spectrum was subjected to spectrum analysis (peak deconvolution), the maximum half width (FWHM) of the peak shown in the region of -10 to 10 ppm was 0 2. The positive electrode active material according to claim 1, wherein the amount of ZnO is 50 ppm or less.
7. The positive electrode active material according to claim 1, wherein the positive electrode active material contains 85 mol % to 95 mol % of nickel based on the total number of moles of remaining metals other than lithium.
8. 2. The positive electrode active material according to claim 1, wherein the positive electrode active material contains 90 mol % to 95 mol % of nickel based on the total number of moles of remaining metals other than lithium.
9. 2. The positive electrode active material of claim 1, wherein the positive electrode active material comprises 0.5 mol % to 5 mol % manganese and 0.5 mol % to 5 mol % aluminum, based on the total number of moles of remaining metals other than lithium.
10. The positive electrode active material according to claim 1, having a composition represented by the following [Chemical Formula 1]: [Chemical formula 1] Li a Ni b Co c Mn d Al e M 1 f O 2 In the above [Chemical Formula 1], M 1 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0.8≦a≦1.2, 0.85≦b≦0.97, 0.02≦c≦0.05, 0.005≦d<0.05, 0.005≦e<0.05, and 0≦f≦0.
02.
11. A first step of forming a precursor by co-precipitation of an aqueous transition metal solution containing nickel ions, cobalt ions, and manganese ions; a second step of mixing the precursor, a lithium source material and an aluminum source material, and then calcining the mixture to form a lithium composite transition metal oxide; and a third step of mixing the lithium transition metal composite oxide and a cobalt raw material, followed by heat treatment to produce a positive electrode active material.
12. The method for producing a positive electrode active material according to claim 11, wherein the ratio of the number of moles of cobalt contained in the cobalt source material in the third step to the number of moles of cobalt contained in the precursor in the first step is 1 to 1.
5.
13. The method for producing a positive electrode active material according to claim 11, wherein in the third step, the heat treatment temperature is 600° C. to 750° C.
14. A positive electrode comprising the positive electrode active material according to claim 1 .
15. A lithium secondary battery comprising the positive electrode according to claim 14.
Citation Information
Patent Citations
Cathode active material precursor for secondary battery, preparation method therefor, and method for preparing cathode active material
CN113748541A
Lithium-metal composite oxide and electrochemical device using the same
JP2009526736A
Lithium titanium oxide, method of manufacturing the same, negative electrode including the same, and lithium battery employing the same
JP2013159555A
Positive electrode active material for lithium secondary battery, method for preparing the same, and lithium secondary battery including the same
KR1020180077090A
KR20200090661A